2019
DOI: 10.3390/su11174514
|View full text |Cite
|
Sign up to set email alerts
|

How Gender, Age and Education Influence the Entrepreneur’s Social Orientation: The Moderating Effect of Economic Development

Abstract: A social entrepreneur is an individual that creates a company to generate social value. Social entrepreneurs tend to develop these initiatives because they have a strong social orientation. The reason why people have a stronger or weaker social orientation has been analyzed through the lens of different subjects, among biological, social, and behavioral sciences. However, the literature does not agree about which variables influence individuals to have more or less social orientation. We investigated which var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 46 publications
0
19
2
4
Order By: Relevance
“…According to Ciaian and co-authors [59], Portugal in 2007 had one of the lowest leased land rates in EU, under 25% of the used agricultural area (UAA). The positive influence of age and education on entrepreneurship in OF is a central issue, where generational renewal plays a particularly important role for innovation and development [60]. Younger farmers with higher academic and agricultural background have more resources to manage new technologies and deal with the most demanding market competition contexts, creating new development models around the OF concept, based on shared projects with related topics, such as the green and circular economy [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…According to Ciaian and co-authors [59], Portugal in 2007 had one of the lowest leased land rates in EU, under 25% of the used agricultural area (UAA). The positive influence of age and education on entrepreneurship in OF is a central issue, where generational renewal plays a particularly important role for innovation and development [60]. Younger farmers with higher academic and agricultural background have more resources to manage new technologies and deal with the most demanding market competition contexts, creating new development models around the OF concept, based on shared projects with related topics, such as the green and circular economy [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the social orientation of entrepreneurs found that this is stronger in women, in the more educated, and in older people, although the latter required further research (Marín et al, 2019). Although gender is considered to be an important factor in determining attitudes to ethics, a study by Serwinek (1992) failed to detect any strong differences in perception between men and women.…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…Many studies have also found that demographic factors, such as the gender, age and education of entrepreneurs, influence ethical business management (Dalton & Ortegren, 2011;Marín, Nicolás & Rubio, 2019;Peterson, Rhoads & Vaught, 2001;Serwinek, 1992). It is therefore relevant to study how these and other demographic factors influence the perception and implementation of business ethics and the ethical behaviour of entrepreneurs, business owners and managers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Pero no sólo ello, aparte de su trabajo retribuido, también eran trabajadoras dentro del hogar, manteniendo las funciones que se les atribuyen por cuestión de género (Nicolás y Rubio, 2016;Navarro et al, 2018b). Por tanto, eran madres de familia y responsables de la mayoría de las tareas domésticas (Marín et al, 2019). Aunque el resto de los miembros "colaboraba", las tareas del hogar seguían sin repartirse equitativamente.…”
Section: Conclusionesunclassified